Attention and the Art of Scientific Publishing - Arjo Klamer; Hendrik P. van Dalen (Tinbergen Institute, 2001)
Attention is the coordination device, which makes modern science workthe way it does. A typical characteristic of attention in thescientific world is that those who seek attention are the same peoplewho are giving it. Another important feature within groups is theskewed distribution of attention. We discuss the effect thesecharacteristics have on scientific institutions. An important thesisis that scientists converge in clusters of likeminded scientists.Given the character of scientific organisation and communication weexpect that the digitalisation of scientific communication will notaffect the basic scientific institutions as the principles upon whichthe Internet and open source code projects function coincide more orless with the way science functions. The channelling of attentionwill remain an important issue as the flood of information in the ageof electronic publishing will only increase.
Keywords: 330; Bibliometrie; Internet; Theorie